Genetic Diversity of Pineapple (Ananas comosus) Germplasm in Malaysia Using Simple Sequence Repeat (SSR) Markers - Siti Norhayati Ismail; Nurul Shamimi Abdul Ghani; Shahril Firdaus Ab. Razak; Rabiatul Adawiah Zainal Abidin; Muhammad Fairuz Mohd Yusof; Mohd Nizam Zubir; Rozlaily Zainol (Tropical Life Sciences Research, 2020)
Assessments of genetic diversity have been claimed to be significantly efficient in utilising and managing resources of genetic for breeding programme. In this study, variations in genetic were observed in 65 pineapple accessions gathered from germplasm available at Malaysian Agriculture Research and Development Institute (MARDI) located in Pontian, Johor via 15 markers of simple sequence repeat (SSR). The results showed that 59 alleles appeared to range from 2.0 to 6.0 alleles with a mean of 3.9 alleles per locus, thus displaying polymorphism for all samples at a moderate level. Furthermore, the values of polymorphic information content (PIC) had been found to range between 0.104 (TsuAC035) and 0.697 (Acom_9.9), thus averaging at the value of 0.433. In addition, the expected and the observed heterozygosity of each locus seemed to vary within the ranges of 0.033 to 0.712, and from 0.033 to 0.885, along with the average values of 0.437 and 0.511, respectively. The population structure analysis via method of delta K (?K), along with mean of L (K) method, revealed that individuals from the germplasm could be divided into two major clusters based on genetics (K = 2), namely Group 1 and Group 2. As such, five accessions (Yankee, SRK Chalok, SCK Giant India, SC KEW5 India and SC1 Thailand) were clustered in Group 1, while the rest were clustered in Group 2. These outcomes were also supported by the dendrogram, which had been generated through the technique of unweighted pair group with arithmetic mean (UPGMA). These analyses appear to be helpful amongst breeders to maintain and to manage their collections of germplasm. Besides, the data gathered in this study can be useful for breeders to exploit the area of genetic diversity in estimating the level of heterosis. Penilaian ke atas diversiti genetik adalah penting bagi penggunaan dan pengurusan sumber genetik yang efisien dalam program pembaikbakaan. Kepelbagaian genetik dapat diperhatikan pada 65 aksesi nanas yang dikumpulkan daripada koleksi janaplasma MARDI yang berada di Pontian, Johor dengan menggunakan 15 penanda simple sequence repeat (SSR). Keputusan menunjukkan sejumlah 59 alel antara 2 hingga 6 dengan purata sebanyak 3.93 alel bagi setiap lokus, dan ini menunjukkan tahap polimorfisma yang sederhana bagi seluruh individu. Selain itu, nilai kandungan maklumat polimorfisma (PIC) yang ditemui adalah antara 0.104 (TsuAC035) hingga 0.697 (Acom_9.9) dengan jumlah purata sebanyak 0.433. Tambahan pula, keheterozigotan yang dijangka dan diperhatikan adalah berbeza antara 0.033 hingga 0.885 dan 0.033 hingga 0.712 dengan purata masing-masing antara 0.511 dan 0.437. Analisa struktur populasi menggunakan kaedah delta K (?K) serta kaedah purata L (K) menunjukkan bahawa individu daripada janaplasma nanas ini dapat dibahagikan kepada dua kumpulan genetik utama (K = 2) yang diberi nama Kumpulan 1 dan Kumpulan 2. Lima aksesi (Yankee, SRK Chalok, SCK Giant India, SC KEW5 India dan SC1 Thailand) telah dikumpulkan di dalam Kumpulan 1 manakala yang selebihnya di dalam Kumpulan 2. Penemuan ini turut disokong oleh dendrogram yang dibina menggunakan kaedah unweighted pair group with arithmetic mean (UPGMA). Analisa ini sangat membantu pembiakbaka dalam mengekalkan dan mengurus koleksi janaplasma mereka. Di samping itu, data-data yang dikumpulkan dalam kajian ini sangat berguna kepada pembiakbaka dalam mengeksploitasikan diversiti genetik bagi menganggar tahap heterosis.